2006
DOI: 10.1002/mds.21140
|View full text |Cite
|
Sign up to set email alerts
|

Hypoperfusion of the visual pathway in parkinsonian patients with visual hallucinations

Abstract: Little is known about the developing mechanisms of visual hallucinations in Parkinson's disease. This study aimed to investigate perfusion changes in parkinsonian patients with visual hallucinations using n-isopropyl-p-[123I]iodoamphetamine ([123I]IMP) single photon emission computed tomography imaging. A total of 70 consecutive patients, including 31 patients with visual hallucinations, and 39 patients without hallucinations, participated in this study. Patients with severe cognitive impairment (Mini-Mental S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 18 publications
7
39
0
1
Order By: Relevance
“…In addition to our own previous 18 F-FDG PET study on VH in PD [1] , in which we reported a significant hypometabolism of brain regions of the 2 visual streams. Matsui et al [26] also described significant functional damage to these visual pathways in hallucinating patients with PD. This finding is also mirrored in a study by Nagano-Saito et al [27] , who also reported a relative metabolic deficit in posterior cortical areas in a hallucinating PD group.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to our own previous 18 F-FDG PET study on VH in PD [1] , in which we reported a significant hypometabolism of brain regions of the 2 visual streams. Matsui et al [26] also described significant functional damage to these visual pathways in hallucinating patients with PD. This finding is also mirrored in a study by Nagano-Saito et al [27] , who also reported a relative metabolic deficit in posterior cortical areas in a hallucinating PD group.…”
Section: Discussionmentioning
confidence: 96%
“…One study reported hyperperfusion of the right superior and middle temporal gyri in PD patients with VH 6 , whereas the other study found that hallucinating PD patients exhibited hypoperfusion in the bilateral inferior parietal lobules and inferior temporal gyrus 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Visual hallucination in PD patients is an important risk factor in terms of nursing home placement, poor quality of life, and mortality 4 . Neuroimaging studies suggested that brain regions involved in higher-order visual processing, ventral or dorsal pathways, were associated with VH in PD patients [5][6][7][8][9] . Pathologic study in Lewy body (LB) disease reported a striking association between the distribution of temporal lobe LB and VH 10 .…”
mentioning
confidence: 99%
“…In terms of early intervention, it is important to determine which patterns on the [ 18 F]-FDG PET scans of iRBD patients are suggestive of underlying prodromal DLB or PD. A single photon emission computed tomography imaging study showed that PD patients with visual hallucinations had perfusion reductions in the bilateral inferior parietal lobule, inferior temporal gyrus, precuneus gyrus and occipital cortex (Matsui et al, 2006). In a cerebral SPECT study (Shirakawa et al, 2002) that compared iRBD patients with a control group, a statistically significant decrease in blood flow was observed in the upper portion of the frontal lobe on the left and right sides and the pons in the iRBD group.…”
Section: Pet and Spectmentioning
confidence: 99%